Computational organizational cognition : a study on thinking and action in organizations - Secchi, Davide (Emerald Publishing Limited, 2021)
In Computational Organizational Cognition, Davide Secchi presents an innovative definition of organizational cognition using a research tradition that builds on the Embodied/Distributed/Extended Cognition (EDEC) perspectives and it is developed through agent-based computational simulation modelling. After an overview of EDEC perspectives, Computational Organizational Cognition presents four simulations which allow readers to clearly assess the advantages of agent-based computational organizational cognition (AOC) for both theory and practice. The book attempts to demonstrate how AOC is a useful if not essential instrument to explore, understand and analyze the inner complexities of organizational cognition. AOC is a powerful tool and an approach for organizational research enquiry at the service of both organizational scholars and cognitive scientists.
Includes index.
Keywords: Corporate culture.; Information technology.; Business -- Data processing.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books